Gender-specific efficacy revealed by head-to-head comparison of pasireotide and octreotide in a representative in vivo model of nonfunctioning pituitary tumors - Gulde, Sebastian; Wiedemann, Tobias; Schillmaier, Mathias; Valença, Isabel; Lupp, Amelie; Steiger, Katja; Yen, Hsi-Yu; Bäuerle, Stephen; Notni, Johannes; Luque, Raul; Schmid, Herbert; Schulz, Stefan; et al. (Cancers, 2021)
Invasive nonfunctioning pituitary tumors (NFPTs) are non-resectable neoplasms associated with frequent relapse and significant comorbidities. Current treatments, including somatostatin receptor 2 (SSTR2)-directed somatostatin analogs (SSAs), often fail against NFPTs. Thus, identifying effective therapies is clinically relevant. As NFPTs express SSTR3 at high levels, pasireotide, a multireceptor-targeted SSA, might be beneficial. Here we evaluated pasireotide in the only representative model of spontaneous NFPTs (MENX rats) in vivo. Octreotide long-acting release (LAR), pasireotide LAR, or placebo, were administered to age-matched, tumor-bearing MENX rats of both sexes for 28 d or 56 d. Longitudinal high-resolution magnetic resonance imaging monitored tumor growth. While tumors in placebo-treated rats increased in volume over time, PTs in drug-treated rats displayed significant growth suppression, and occasional tumor shrinkage. Pasireotide elicited stronger growth inhibition. Radiological responses correlated with tumors’ proliferation rates. Both SSAs, but especially pasireotide, were more effective in female vs. male rats. Basal Sstr3 expression was significantly higher in the former group. It is noteworthy that female human NFPTs patients also have a trend towards higher SSTR3 expression. Altogether, our studies provide the rationale for testing pasireotide in patients with residual/recurrent NFPTs. If confirmed, the sex-related SSTR3 expression might be used as criteria to stratify NFPTs patients for treatment with pasireotide.